Detection and biocontrol of Tobamovirus tabaci infecting tomato in Iraq - Ahmed, Hind Jassim; Al-Kuwaiti, Nawres Abdulelah Sadeq (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
The antiviral activity of leaf extracts from Datura stramonium and tomato plants inoculated with TMV, combined with 20% skimmed milk, was investigated. A TMV isolate was confirmed using bioassay, serological, and molecular approaches and subsequently used to inoculate plants. Tomato plants, both pre- and post-inoculated with TMV, were sprayed with leaf extracts from either TMV-free or infected plants, alone or mixed with 20% skimmed milk. Enzyme-linked immunosorbent assay (ELISA) using tobamovirus-specific antibodies and local lesion tests were conducted to assess antiviral activity based on virus concentration and infectivity in treated plants. The experiment followed a completely randomized design (CRD), and the Least Significant Difference (LSD) test was applied to evaluate ELISA optical density (OD) values. OD data revealed that the combination treatment (inoculated tomato leaf extract + 20% skimmed milk) inhibited TMV in tomato plants by up to 56%, showing the highest antiviral activity. This study is the first to investigate the antiviral potential of leaf extracts from TMV-infected plants.